Research and development management : technology journey through analysis, forecasting and decision making - Daim, Tugrul Unsal, 1967-; Kim, Jisun, 1973-; Phan, Kenny (Science, technology and innovation studies., 2017)
This book introduces readers to essential technology assessment and forecasting tools, demonstrating their use on the basis of multiple cases. As organizations in the high-tech industry need to be able to assess emerging technologies, the book presents cases in which formal decision-making models are developed, providing a framework for decision-making in the context of technology acquisition and development. Applications of different technology forecasting tools are also discussed for a range of technologies and sectors, providing a guide to keep R & D organizations abreast of technological trends that affect their business. As such, the book offers a valuable the theoretical and practical reference guide for R & D managers responsible for emerging and future technologies.